The Development Of Environmental Mobile Learning (EML) For Learning Media In High School Based On The Natural Resources In Mangkunagoro I Forest Park - Siti Siwi Wulandari; Nurmiyati Nurmiyati; Muzzazinah Muzzazinah; Alanindra Saputra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
Introduction: Environmental changes is the last topic in tenth-grade senior high school. This topic can be studied more interestingly when the teacher can present some factual phenomenons all around.This research examined the development of the EML (Environment Mobile Learning) app. Purposes: This research was aimed to (1) Exploits the Mangkunagoro I Forest Park as an instructional media source for Biology learning; (2) Develop an Android-based EML (Environment Mobile Learning) app for learning about environmental changestopic for high school students; (3) Test the feasibility of an Android-based EML (Environment Mobile Learning) app as a learning media for Biology. Methods: The research was a combination of the biological research in Mangkunegoro I Forest Park, and R&D research for the development of the EML app. The ADDIE model by Branch (2009) was used as the research method. The research object was the EML app. The subjects of this study were two media experts, two subject matter experts, a learning expert, two teachers, and tenth graders from one high school in Surakarta. The samples taken from the Forest Park were collected using explorative methods, and the students were selected using purposive random sampling. The data was collected using observations, interviews, and questionnaires. The data collected from Forest Park were analyzed using qualitative descriptive methods. The data were validated and analyzed based on the experts’ judgments. The data from student trials were analyzed using Rasch Models. Results: The result showed (1) The samples and data from the Forest Park were used as EML’s content; (2) The validation result showed that media experts gave a score of 89,58%, the material experts gave 87,5%, 96,13% from learning expert, and 81,55% from Biology teachers; (3) The Rasch Model showed the person reliability score of 0.85, item reliability of 0.87, and 0.87 for Alpha Cronbach. Conclusion: It concluded the EML was suitable as media to learn about environmental changes